Strategi Melestarikan Budaya Indonesia di Era Modern - Habel Nain Samongilailai; Aldrin Budi Utomo (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Indonesia, known for its diverse traditions and cultures, provides an interesting example of unity amidst diversity. This research explores the profound impact of culture on individual identity and societal development. By analyzing the evolution of Indonesian culture, from traditional practices to modern influences, we uncover the challenges faced due to globalization and the importance of cultural preservation. The research emphasizes the need for collaboration in protecting Indonesia's cultural heritage, highlighting the role of education, awareness, and government policy in keeping valuable traditions alive.